2021
DOI: 10.1021/acsaem.1c00128
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced H2 Evolution by Hexaniobate Sheets Grafted with Metal Ions: The Fate of Photogenerated Carriers

Abstract: Layered niobates are well-known photocatalysts for H2 evolution with a rich surface chemistry. Their photoactivity, however, is limited by their wide band gap energy (∼3.5 eV) and partial deactivation due to surface poisoning by photogenerated H2O2. In this way, a surface modification method able to induce novel electronic processes without changing the bulk properties can improve their performance. In this work, the surface of exfoliated hexaniobate (K4–x H x Nb6O17) layers was modified by grafting with metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
(129 reference statements)
1
12
0
Order By: Relevance
“…Additionally, amorphous clusters could be observed on the surface of the grafted sample, as highlighted by the arrows, which are not present on the pristine hexaniobate. Such nanoclusters have been observed by our group for Co(II) and Fe(III)-grafted hexaniobates [12] and also for TiO 2 nanoparticles grafted with Cu(II) ions. [22,23] Therefore, it seems most of Cu + 2 ions remains at the surface to form amorphous clusters of around 10 nm length.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Additionally, amorphous clusters could be observed on the surface of the grafted sample, as highlighted by the arrows, which are not present on the pristine hexaniobate. Such nanoclusters have been observed by our group for Co(II) and Fe(III)-grafted hexaniobates [12] and also for TiO 2 nanoparticles grafted with Cu(II) ions. [22,23] Therefore, it seems most of Cu + 2 ions remains at the surface to form amorphous clusters of around 10 nm length.…”
Section: Resultssupporting
confidence: 69%
“…As described previously, [12,18] potassium hexaniobate prepared by solid state reaction exhibits a structure corresponding to K 4 Nb 6 O 17 .3H 2 O (JCPDS 21-1297). Following exfoliation with tetrabutylammonium hydroxide, an increase in the surface area is observed, but the crystallinity is lost as the well-ordered stacked layers became randomly organized.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, layered niobates have gained a great deal of attention in photocatalytic water splitting owning to their various electronic and structural features and high stability. Foordite SnNb 2 O 6 as a typical layered niobate has gained great attention in photocatalytic applications due to its suitable band gap (∼2.3 eV) and proper band location. To date, various methodologies have been adopted to prepare nanostructured SnNb 2 O 6 , such as the hydrothermal method, , the microwave-assisted hydrothermal method, the solvothermal method, and the flux-assisted method. , Wu et al demonstrated that ultrathin SnNb 2 O 6 nanosheets prepared by a microwave-assisted hydrothermal method exhibited excellent visible light driven photocatalytic performance for degradation of organic pollution . Unfortunately, the aforementioned hydrothermal method toward the synthesis of SnNb 2 O 6 nanosheets required the use of the environmentally unfriendly solvent hydrofluoric acid (HF).…”
Section: Introductionmentioning
confidence: 99%